Crisis? What crisis? Anatomy of the regulatory failure in finance - Jakob Vestergaard (Danish Institute for International Studies (DIIS), 2008)
Despite the global financial crisis and the prospect of severe economic recession, debates on future financial regulation take little if any notice of reasons why the previous regime of financial regulation failed so spectacularly. The paper identifies the key presumptions underlying efforts to strengthen the 'international financial architecture' (IFA) over the past decade. At the core of the IFA is a set of standards of 'best practice' and the assumption that 'market dis-cipline' rewards and punishes economies according to their degree of compliance with standards. Further, the IFA assumes that 'market-sensitive' risk management promotes the resilience of the international financial system and that the 'soundness' of financial systems may be assessed by aggregating measures of the soundness of individual financial institutions. Historical analysis of the correlation between international capital flows and domestic policy reforms, as well as quanti-tative studies of the correlation between compliance and the cost of capital, demonstrates that financial markets by no means reward and punish economies in accordance with compliance. Evidence further suggests that the current approach to detecting financial vulnerability is mislead-ing and that the promotion of 'market sensitive' risk management undermines rather than in-creases the stability and resilience of the international financial system.
Keywords: 330; Internationaler Finanzmarkt; Internationales Währungssystem; Regulierung; Finanzmarktkrise; Welt